Pengaruh Penggunaan Blower & Es Batu Pada Alat Simulasi Ventilasi Tambang Bawah Tanah Dalam Upaya Penurunan Suhu Untuk Skala Laboratorium - Wuni Aprila; Bambang Heriyadi; Heri Prabowo; Jukepsa Andas (Journals Mining Engineering : Bina Tambang, 2023)
Increased temperatures in Underground Mines can cause uncomfortable working conditions and negatively impact workers' health. If there is a temperature or increase in temperature that exceeds the standards determined by the Decree of the Director General of Minerals and Coal, Ministry of Mineral Resources and Mineral Resources No. 185.K/30DJB/2019, it is important to identify efforts to reduce the temperature in the work environment. This research wants to reveal the effect of using ice cubes to reduce the temperature which is simulated in an underground mine ventilation simulation tool in the laboratory, then the results obtained will be implemented in field conditions and the results will be correlated with needs in the field. The data taken to obtain results using a simulation tool in the laboratory was done using 2 experiments, where experiment 1 used 2 kg of ice cubes, at dry temperatures it could not reduce 1°C while at wet temperatures it could reduce ±1°C. Then in experiment 2 using 5kg ice cubes, the results showed that the dry temperature could decrease by ± 1°C and the wet temperature could decrease by ± 2°C. For humidity when using ice cubes there is not much change, only around ±5% but still remains within the threshold value.The correlation results when placed in the field from simulation tools in the laboratory are that in experiment 1 it requires 25 kg of ice cubes to reduce 1°C in wet temperature only, and in experiment 2 it requires 61 kg of ice cubes to reduce 1°C in dry temperature and 2°C at wet temperatures.To obtain correlation results, they are placed in field conditions in accordance with established standards, for Tunnel A location requires 183 kg of ice cubes, Tunnel B 244 kg of ice cubes, Tunnel A to Tunnel B as much as 183 kg of ice cubes, Branch 1 Tunnel 2 had 244 kg of ice cubes and Branch 2 Tunnel B had 305 ice cubes.